Studi Awal Komunitas Ordo Anura di Kawasan Ekowisata Sawangan, Magelang, Jawa Tengah - Tony Febri Qurniawan; Hestin Ambar Asti; Rury Eprilurahman (Fakultas Biologi | Universitas Jenderal Soedirman, 2010)
Frogs and toads (Amphibia: Anura) were very sensitive to environmental changes. Due to their sensitivity, usually they can be used as indicator for environmental changes. On the other hands, there has been only limited data on the diversity and distribution of frogs and toads in Java. This could lead to the reducing population of frogs and toads in Java. Based on those facts, this research was aimed to collect data on species diversity, species richness, species composition and species distribution of frogs and toad from Sawangan Ecotourism, Magelang, Central Java Province. This study was expected to complete the database of anurans in Central Java. The research was conducted from June to July 2009, mostly at night. The VES (Visual Encounter Survey) method combined with 200 m transects were used for sampling. Seven species of anurans were recorded during the survey. They were Duttaphrynus melanostictus, Limnonectes kuhlii, Limnonectes microdiscus, Microhyla achatina, Odorrana hosii, Hylarana chalconotus and Huia masonii. From those seven species, only three (Huia masonii, Microhyla achatina and Limnonectes kuhlii) were known as endemic of Java.